CO excitation in the Seyfert galaxy NGC 7130. (23rd May 2017) - Pozzi, F.; Vallini, L.; Vignali, C.; Talia, M.; Gruppioni, C.; Mingozzi, M.; Massardi, M.; Andreani, P.
Abstract: We present a coherent multiband modelling of the carbon monoxide (CO) spectral energy distribution of the local Seyfert galaxy NGC 7130 to assess the impact of the active galactic nucleus (AGN) activity on the molecular gas. We take advantage of all the available data from X-ray to the submillimetre, including ALMA data. The high-resolution (∼0.2 arcsec) ALMA CO(6–5) data constrain the spatial extension of the CO emission down to an ∼70 pc scale. From the analysis of the archival Chandra and NuSTAR data, we infer the presence of a buried, Compton-thick AGN of moderate luminosity, L 2–10 keV   ∼ 1.6 × 10 43  erg s −1 . We explore photodissociation and X-ray-dominated-region (PDR and XDR) models to reproduce the CO emission. We find that PDRs can reproduce the CO lines up to J  ∼ 6; however, the higher rotational ladder requires the presence of a separate source of excitation. We consider X-ray heating by the AGNs as a source of excitation, and find that it can reproduce the observed CO spectral energy distribution. By adopting a composite PDR+XDR model, we derive molecular cloud properties. Our study clearly indicates the capabilities offered by the current generation of instruments to shed light on the properties of nearby galaxies by adopting state-of-the-art physical modelling.